2021
DOI: 10.3344/kjp.2021.34.3.288
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter survey of symptoms, work life, economic status, and quality of life of complex regional pain syndrome patients

Abstract: Background: Complex regional pain syndrome (CRPS) is an intractable pain disease with various symptoms. Here, we investigated the disease status, work life, sleep problems, medical insurance, economic status, psychological problems, and quality of life (QOL) of CRPS patients. Methods: CRPS patients from 37 university hospitals in South Korea were surveyed. The survey questionnaire consisted of 24 questions on the following aspects of CRPS patients: sex, age, occupation, cause of injury, activities of daily liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The close relationship between mental disorders and chronic diseases has been widely accepted. Most patients with chronic diseases have psychological problems, which are not conducive to the recovery of the disease [ 11 ]. The cluster nursing mode attaches importance to psychological nursing, evaluates the psychological needs of patients, and then adopts targeted psychological nursing, communicates with patients more, understands the real thoughts of patients, establishes good feelings with patients, makes patients trust nursing staff, relieves patients' bad psychological emotions, and keeps them in a good psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship between mental disorders and chronic diseases has been widely accepted. Most patients with chronic diseases have psychological problems, which are not conducive to the recovery of the disease [ 11 ]. The cluster nursing mode attaches importance to psychological nursing, evaluates the psychological needs of patients, and then adopts targeted psychological nursing, communicates with patients more, understands the real thoughts of patients, establishes good feelings with patients, makes patients trust nursing staff, relieves patients' bad psychological emotions, and keeps them in a good psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a relatively large decrease was observed in patients with PHN. It can be inferred that due to the relatively severe level of pain and physical limitations in CRPS patients [ 23 , 26 , 27 ], the decrease was less prominent in them than in others, regardless of their COVID-19 concerns. CRPS patients also hesitate to exercise and rarely go out much due to their severe pain [ 28 ]; thus, their activity could not decrease significantly more.…”
Section: Discussionmentioning
confidence: 99%
“…The WHOQOL-BREF questionnaire is frequently used to evaluate the effectiveness of therapeutic regimens and psychological interventions for chronic diseases [ 24 ]. In the present study, the mean total score (including all four domains: physical health, psychological health, social relationships, and environment) was lower (42/80) than those of Taiwanese and Iranian patients with lower back pain (both 53/80) [ 30 ], but higher than that of Korean patients with complex regional pain syndrome (33.5/80) [ 31 ]. In the present study, 60% of the patients reported constipation as the most troublesome side effect; this rate is higher than that (47%) in a study of Taiwanese patients receiving long-term opioid therapy in 2010 [ 18 ].…”
Section: Discussionmentioning
confidence: 79%